2020
DOI: 10.1038/s41398-020-0792-z
|View full text |Cite
|
Sign up to set email alerts
|

Altered anterior cingulate glutamatergic metabolism in depressed adolescents with current suicidal ideation

Abstract: The anterior cingulate cortex (ACC) is involved in emotion regulation and salience processing. Prior research has implicated ACC dysfunction in suicidal ideation (SI) and suicidal behavior. This study aimed to quantify ACC glutamatergic concentrations and to examine relationships with SI in a sample of healthy and depressed adolescents. Forty adolescents underwent clinical evaluation and proton magnetic resonance spectroscopy (1 H-MRS) at 3 T, utilizing a 2-dimensional J-averaged PRESS sequence sampling a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 95 publications
0
23
0
Order By: Relevance
“…We focused on the dorsal division of the ACC based on findings of previous studies that abnormalities in this region may be a neurodevelopmentally sensitive marker of adolescent depression (28), in contrast to the rostral (pregenual) or medial ACC (22). Studies focused on the rostral and medial ACC in depressed adolescents, however, have found evidence of higher Glx (sum of glutamate and glutamine, a precursor to glutamate and GABA) in depressed adolescents with suicidal ideation than in healthy controls (53), as well as reductions in the ratio of glutamine to glutamate (Gln/Glu) in response to treatment-related symptom improvement (54). Although these studies examined Glx and Gln/Glu rather than solely Glu, their data are nonetheless consistent with our findings that higher levels of Glu may contribute to depressive symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the dorsal division of the ACC based on findings of previous studies that abnormalities in this region may be a neurodevelopmentally sensitive marker of adolescent depression (28), in contrast to the rostral (pregenual) or medial ACC (22). Studies focused on the rostral and medial ACC in depressed adolescents, however, have found evidence of higher Glx (sum of glutamate and glutamine, a precursor to glutamate and GABA) in depressed adolescents with suicidal ideation than in healthy controls (53), as well as reductions in the ratio of glutamine to glutamate (Gln/Glu) in response to treatment-related symptom improvement (54). Although these studies examined Glx and Gln/Glu rather than solely Glu, their data are nonetheless consistent with our findings that higher levels of Glu may contribute to depressive symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate level was reported to be decreased together with myo-inositol (a glial marker) and NAA in ACC of depressed subjects ( 120 , 126 ). Reduced levels of Glx and glutamine have also been reported in the hippocampus of unipolar MDD subjects ( 121 ).…”
Section: Neurometabolites Homeostasis and Metabolism In Depressionmentioning
confidence: 99%
“…Although the physiological role of NAA in neural function is unclear, it is typically associated with neuronal integrity and mitochondrial health ( 158 ). Reduced level of NAA is reported in different brain regions of depressed subjects, including PFC ( 112 , 113 ), ACC ( 120 , 126 ), right frontal and parietal lobe ( 108 ), and in the hippocampus ( 122 , 159 ) ( Tables 1 , 2 ). A lower level of NAA has also been seen in the hippocampus ( 122 ), nucleus accumbens ( 110 ) and PFC ( 112 , 116 ) of rodent models of depression.…”
Section: Neurometabolites Homeostasis and Metabolism In Depressionmentioning
confidence: 99%
“…Interestingly, previous studies also reported some protein and metabolite biomarkers for suicidal behaviors in the brain regions with functional connectome alternations and the peripheral blood [ 88 92 ]. These proteins, neurotransmitters, and metabolites are primarily related to neurogenesis, neurometabolism, synaptic plasticity, and immune-inflammatory processes (Fig.…”
Section: Brain Functional Connectome For Predicting Suicide Risks In Mdd Patientsmentioning
confidence: 99%